2010
DOI: 10.1111/j.1399-3054.2009.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in thermotolerance are dependent upon prestress capacity for antioxidant protection of the photosynthetic apparatus inGossypium hirsutum

Abstract: Numerous studies have illustrated the need for antioxidant enzymes in acquired photosynthetic thermotolerance, but information on their possible role in promoting innate thermotolerance is lacking. We investigated the hypothesis that genotypic differences in source leaf photosynthetic thermostability would be dependent upon prestress capacity for antioxidant protection of the photosynthetic apparatus in Gossypium hirsutum. To test this hypothesis, thermosensitive (cv. ST4554) and reportedly thermotolerant (cv.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 41 publications
8
63
0
Order By: Relevance
“…The production and the detoxification of reactive oxygen species (ROS) are important processes in plants exposed to drought and/or heat (Mittler and Zilinskas, 1994;Munne-Bosch et al, 2001;Mittler, 2002;Apel and Hirt, 2004;Reddy et al, 2004;Locato et al, 2008Locato et al, , 2009Simova-Stoilova et al, 2009;Snider et al, 2010;Osorio et al, 2011;Xu et al, 2013). ROS production is increased under abiotic stresses (energy dissipation) and as a consequence cellular constituents including proteins and membrane lipids may be damaged (Mittler, 2002).…”
Section: Reactive Oxygen Species and Protection Of Chloroplast Constimentioning
confidence: 99%
See 1 more Smart Citation
“…The production and the detoxification of reactive oxygen species (ROS) are important processes in plants exposed to drought and/or heat (Mittler and Zilinskas, 1994;Munne-Bosch et al, 2001;Mittler, 2002;Apel and Hirt, 2004;Reddy et al, 2004;Locato et al, 2008Locato et al, , 2009Simova-Stoilova et al, 2009;Snider et al, 2010;Osorio et al, 2011;Xu et al, 2013). ROS production is increased under abiotic stresses (energy dissipation) and as a consequence cellular constituents including proteins and membrane lipids may be damaged (Mittler, 2002).…”
Section: Reactive Oxygen Species and Protection Of Chloroplast Constimentioning
confidence: 99%
“…Therefore ROS detoxification by enzymes (Xiao et al, 2008 ;Bian and Jiang, 2009;Fan et al, 2012;Salazar-Parra et al, 2012 ;Demeter et al, 2014;Sekmen et al, 2014;Song et al, 2014) or low molecular-weight compounds (Mittler, 2002) is essential for the functionality of leaf cells under abiotic stress. The xanthophyll cycle represents a plastid-specific ROS detoxification mechanism (Gallé et al, 2007;Haldimann et al, 2008;de la Rosa-Manzano et al, 2015), while other ROS detoxifying systems (e. g. superoxide dismutases) are present in several subcellular compartments (Locato et al, 2009;Simova-Stoilova et al, 2009;Snider et al, 2010;Song et al, 2014). The accumulation and compartmentation of some metabolites (expecially of ROS scavengers and of compatible solutes such as proline, betain or glycinebetaine which are also important for osmoregulation) help to protect cells from damages caused by heat or drought and to maintain basic cellular functions (Hormaetxe et al, 2007;Wang et al, 2010;Albert et al, 2012;Hu et al, 2013;Wujeska et al, 2013: AbdElgawad et al, 2015Grant et al, 2015).…”
Section: Reactive Oxygen Species and Protection Of Chloroplast Constimentioning
confidence: 99%
“…It was shown that the innate threshold temperature was dependent upon endogenous SOD and glutathione reductase activity in Gossypium hirsutum plants [20]. Under identical growth conditions, thermotolerant G. hirsutum plants had significantly higher optimal and threshold temperatures for the actual quantum yield response of photosystem II and glutathione reductase activity than thermosensitive ones.…”
mentioning
confidence: 97%
“…It was documented that results of the heat tolerance test (short-time growth under 42 º Ñ in growth chamber) positively correlated with improvement of high temperature resistance in field trial [3]. We analyzed such physiological and biochemical parameters which are usually used to characterize the properties of plants under stress as relative water content [14,15], electrolyte leakage [15,16], photosynthetic pigment content and ratios [15,[17][18][19], SOD activity [3,20,21].…”
mentioning
confidence: 99%
“…Antioxidant enzyme activities such as catalases, peroxidases and superoxide dismutases play important role in the detoxification of ROS (Selote et al, 2004;Pastore et al, 2007;Bian and Jiang, 2009). A study on cotton varieties differing in thermotolerance suggests that there is a potential to incorporate the knowledge regarding the role of antioxidant enzymes in stress response for breeding of tolerant varieties (Snider et al, 2010) by the enhancement of in vivo levels of antioxidant enzymes. The relevance of high constitutive activities of ROS-detoxifying enzymes and of their on-going increase during abiotic stress was reported by Turkan et al (2005) for bean plants.…”
Section: Accumulation and Detoxification Of Reactive Oxygen Speciesmentioning
confidence: 99%